ANALISIS KETEPATAN WAKTU LULUS MAHASISWA DENGAN KEMAMPUAN MANAJERIAL YANG BAIK - Asbui; Mukhtar; Kasful Anwar; Mahmud MY (Jurnal Genta Mulia, 2024)
This article aims to determine how managerial skills and time management by the head of the study program affect timely graduation of students. Managerial skills and time management by the head of the program will be one of the factors that determine the ease for students, of course, not apart from several inhibiting and supporting factors. This type of research is quantitative research, the subject of this literature study is the head of the study program, while the object of this research is managerial skills and time management. The technique used to collect data, the author uses literature study. The purpose of this article is to analyze students who are able to complete their studies on time with various busyness, both as employees or as entrepreneurs.